Land Suitability Criteria for Intensively Managed Cavendish Banana Crop in Way Kambas East Lampung, Indonesia - Ansyori, .; Sudarsono, .; Poerwanto, Roedhy; Darmawan, . (JOURNAL OF TROPICAL SOILS, 2010)
Land Suitability Criteria for Intensively Managed  Cavendish Banana Crop in Way Kambas East Lampung, Indonesia (Ansyori, Sudarsono, R Poerwanto, and Darmawan): Banana as one of the pre-eminent products of horticultural crop has a very important role in the growth of agricultural sector.  The research aimed to study the land characteristics which influence the Cavendish banana crop yield and proposing the land suitability classification criteria for the land utilization type of Cavendish banana crop with intensive management which has been tested based on the production rate in the field.  For this purpose, there were 36 observation land units specifically designed by considering factors such as soil subgroups, slopes, land utilization types, and land productivity levels.  At each observation land unit, the land utilization types and land characteristics were indentified.  The relation between land characteristics and production was tested with correlation and regression analysis.  The results of some statistical tests were contrasted and then selected as the basis to develop the land suitability classification criteria for Cavendish banana crop which was intensively managed.  The research findings indicated that the banana crop yield levels were significantly influenced and determined by the land characteristics of soil bulk density, cation exchange capacity, soil permeability, total porosity, exchangeable sodium percentage, soil textural class, and soil erodibility.